Peran Regulasi Dan Standar Internasional (Aaoifi Dan Ifsb) Dalam Pengembangan Perbankan Syariah Di Indonesia - Safnah Soleha; M. Aidil Syahputra; Afni Haryanti Harahap; Khaidar rahmaini jamila (CV. ITTC INDONESIA, 2025)
Islamic banking in Indonesia is growing rapidly, but still faces challenges in harmonizing regulations and strengthening governance. At the international level, the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and the Islamic Financial Services Board (IFSB) play a role in providing standards aimed at improving transparency, accountability, and stability of the Islamic financial system. This study aims to analyze the role of AAOIFI and IFSB standards in the development of Islamic banking in Indonesia and identify challenges in their implementation. This study used a literature review method, examining scientific journals, academic books, and official regulatory documents. The results show that Indonesia implements AAOIFI and IFSB standards adaptively by integrating their main principles into national regulations. AAOIFI standards contribute to improving the quality of financial reporting, while IFSB standards strengthen the risk management framework for Islamic banking. However, their implementation remains hampered by differences in legal systems, limited human resources, and the dominance of mandatory national regulations. Therefore, a gradual convergence strategy is considered the most relevant approach to optimizing the role of international standards in the development of Indonesian Islamic banking.